Memposisikan Perenungan Filsafat tentang Relasi Alam dan Tuhan dalam Bingkai Paradigma Sains Modern - Imam Amrusi Jailani (IAIN Ponorogo, 2012)
This article is not intended to judge or comment on philosophical ideas about the creation of the cosmos from the perspective of modern science, but merely to serve as a comparison and reflection materials. Accurate assessment of the thoughts of philosophers would not be optimal if the modern scientific approaches is used here because their methods are completely different. The philosophers usually use philosophical or spiritual approaches, while the scientists uses modern science and material approaches. If it has been understood that the qualities manifested by something (not the thing itself) is more interesting, it can be understood that the Islamic cosmology presents a perspective that has no connection with a scientific cosmology because of its constantly changing. Here there is a qualitative correspondence scheme illustrating the relative position between the God, the cosmos, and humans.